THE ROLE OF EXTERNAL MEMBERS IN COMPETENCE COMMITTEES - Eskandar Nadeen (My University, 2026)
Introduction: Competency-based medical education (CBME) is transforming residency training by emphasizing outcomes, including the knowledge, skills, and professional behaviours required for high quality patient care. In Canada, the Royal College of Physicians and Surgeons of Canada (RCPSC) has implemented Competence by Design (CBD) as its national CBME framework. Within CBD, competence committees (CCs) play a critical role in reviewing residents’ progress and making decisions about their advancement. An increasing number of residency programs have begun to include external members in their CC meetings, such as faculty from other departments, researchers, or non-physician healthcare providers (e.g., nurses or social workers). However, scholarly attention to how program CC members and residents perceive external members and the challenges external CC members encounter has been limited. Methods: This qualitative case study was conducted at McMaster University across multiple residency programs. Data were collected through semi-structured interviews with program CC members, external members, and residents, as well as direct observations of CC meetings. All interviews were transcribed, and data were analyzed inductively using Yin’s “working your data from the ground up” strategy. Transcripts were coded and organized; themes were iteratively developed, reviewed, and refined. Results: Five themes were developed: 1) Multiple models and roles of external CC members, 2) Preference for one type of external CC member’s expertise over another, 3) External CC members as promoters of integrity, 4) Facilitators for the inclusion of vi external CC members in CCs, and 5) Practical challenges and structural constraints in the inclusion process of external members in CCs. Conclusion: The findings of this work confirm that external CC members are perceived to be a positive addition to CCs, enhancing decision-making processes. The findings have also identified multiple facilitators and challenges to the inclusion of external members in CCs.
EXPLORING THE ROLE OF EXTERNAL MEMBERS IN COMPETENCE COMMITTEES: A QUALITATIVE CASE STUDY OF RESIDENCY PROGRAMS AT MCMASTER UNIVERSITY